The experience of pain in surgical patients : a cross-cultural study : a thesis...for the degree of Master of Arts in Nursing Studies at Massey University - Madjar, Irena (Massey University, 1981)
The purpose of this study was to describe and compare the experience of pain in surgical patients from two cultural groups, and to identify similarities and differences in their conceptualizations of pain, and attitudes and behavioural responses to pain. An integral part of the study was to generate hypotheses and concepts which may contribute to the formulation of substantive theory in the area of care of patients in acute pain. The design of the study was influenced by a qualitative approach to research, with the basic expectation that explanation would emerge from the data collected. The methodology used was that of supplemented participant-observation. Thirty three adults (20 Anglo-Australians and 13 Yugoslavs), admitted for abdominal surgery to one of three hospitals in Sydney and Wollongong, Australia, were observed throughout their period of hospitalization. In addition, non-structured interviews were conducted with each patient prior to surgery, and prior to discharge from hospital; verbal self-reports, visual analogue scales, and behavioural observation check lists were used; and information about peri-operative interventions (including analgesic drugs) was collected. The findings relate primarily to: (a) the experience of pain in terms of the intensity, duration, and quality of pain, and pain-related behaviours; (b) the relief of pain in terms of the use and perceived effectiveness of analgesic drugs and other pain-relieving measures, with special reference to patient preferences for social company during the experience of pain; and (c) the prospective and retrospective evaluation of the experience in terms of pre-operative fears, fulfilment of expectations, and positive and negative aspects of the experience. The findings support the hypothesis that while some behavioural differences exist between Anglo-Australian and Yugoslav patients, the greatest degree of difference between the two groups is found in their underlying attitudes to pain. In addition, a number of more specific conclusions are presented, followed by a discussion of implications for clinical practice and for further research.
Keywords: Postoperative pain; Surgery; Complications